(untitled) (Archives of Mechanics - Test, 1997)
Electrostatic double layers appear in plasma and semiconductor systems with flow of electric current. The systems display bifurcations, chaos, intermittency and power-law of spectral power density that is 1/f-noise also called flicker noise. Fractal analysis of experimental data recorded in time (time-series analysis) indicates that the plasma dynamic systems are of low dimension. Colored and fractal noise influence on measured data may disqualify that conclusion. A piecewise linear dynamical system is considered to clarify this problem. Bifurcation tree, intermittent chaos and 1/f-noise are revealed by the dynamic system.